PENURUNAN SKALA NYERI PADA PASIEN POST OPEN REDUCTIONAL INTERNAL FIXATION MENGGUNAKAN RELAKSASI NAFAS DALAM DAN TERAPI MUSIK - Pujiarto Pujiarto (LPPM Sikes Panca Bhakti Bandar Lampung, 2018)
Fracture is a term of loss of bone continuity, both total and partial. Surgical actions that are often used to deal with fracture problems are ORIF (Open Reductional Internal Fixation) which is useful for stabilizing fractures. Clinical manifestations arising from ORIF surgery are the onset of feeling of pain. Pain management can be done with pharmacological and non-pharmacological therapy. Deep breath relaxation and music therapy are non-pharmacological therapeutic measures. The aim of this study is to analyze the effects of applying deep breath relaxation and music therapy on decreasing pain scale. The method in this study is a case study by using 2 samples research by taking data through interviews, observations, and documentation and then analyzing the data by revealing the facts then associated with previous theories and research. The results in this study show that deep breathing relaxation and music therapy can reduce scalability in both respondents. Based on the results of deep breath relaxation research and music therapy can be used as one of the pain management for pain problems in post ORIF patients with lower extremities undergoing treatment.